Direction of social work education in Malaysia: strategies to implement good governance - Azizul, Muhammad Dhamir Audi; Amin, Samir Muhazzab (International Organization of Scientific Research, 2019)
The debates on how social work education shapes a good governance widely debated particularly international, but rarely considered together. The author undertook in-depth understanding on this issue by searching related literature to understand how social work education can shapes good governance in Malaysia. This paper analyses five adaptation strategies, namely, restructuring knowledge and skill of academic staff, strengthening social relationship with stakeholder, restructuring pedagogical techniques, implementation community development program, and facilitating the learning of alternative skills. These suggestions are hoped to provide a serious concern to the policy makers, local leaders, and government to concern that social work education is the crucial element to improving good governance in Malaysia.